The Relationship Between Knowledge and Distance to Health Facilities and the Completeness of K6 Prenatal Care Visits - Tri Endah Suryani; Lolli Nababan; Poppy siska Putri; Efrilya Wahyu Suci Wulandari (Jurnal Kebidanan Manna, 2026)
Background: Antenatal Care (ANC) services are a vital maternal health intervention for the early detection of pregnancy risk factors and the prevention of complications contributing to high maternal mortality rates. Although the national target for both the first visit (K1) and complete six visits (K6) is 100%, coverage remains suboptimal. Low knowledge regarding the benefits of prenatal check-ups often hinders adherence. Community Health Center X continues to face low complete K6 coverage at 60.4%. This study aims to analyze the relationship between pregnant women's knowledge level and distance to health facilities with the completeness of K6 ANC visits. Methods: An analytical study with a cross-sectional approach was conducted. The study sample comprised 47 postpartum women selected using total sampling. Data were analyzed using univariate and bivariate statistical analysis. Results: The findings revealed that 55.3% of respondents had not completed the K6 ANC visits, and 48.9% possessed a low level of knowledge regarding prenatal care. Although the majority of respondents (63.8%) had good geographic access living within a reasonable distance, this ease of access did not fully translate into service utilization due to continued reliance on traditional practices. Bivariate analysis demonstrated a significant association between knowledge level and K6 ANC completeness ($p = 0.003$), as well as between distance to health facilities and K6 ANC completeness ($p = 0.002$). Conclusion: Knowledge level, reproductive experience, and geographic accessibility are critical determinants influencing maternal adherence to standard complete antenatal care (K6) visits.